Critical success factors in accepting technology in the classroom - Veiga, Francisco José Miranda (2021)
The adoption of technology on the individual and organizational level may be a necessary condition, but it is not sufficient for the digital transformation, seen as the mobilizing challenge to do something new and different. Without a strategic vision, we take the risk of acquiring resources to do the same as before, essentially changing the format. This inability imprisons the school to inconsequential models, resources and strategies. Interdisciplinary, social and project-based learning that the most advanced technology provides can be adopted. Augmented and virtual reality, the internet of things, robots, artificial intelligence and digital assistants can bring innovation to teaching. But also mobiles, games, simulators and multimedia can inspire collaborative creativity. On the other hand, the pandemic, in terms of the adoption of technology, constitutes a kind of insurrection against the fatalism that it is not possible to restart the system, that is, rethink the school. This study aims at investigating the degree of acceptance, materialized in the use of technology, by teachers of primary and secondary education, in the context of the classroom. As a methodological support to this study, the model “Unified Theory of Acceptance and Use of Technology” (UTAUT)) was used and a questionnaire applied to teachers at our school, obtaining 90 responses. The analysis of the responses reveals that the expected adoption of information technologies currently has a global performance, which becomes the most significant positive influence on the motivation and involvement of teachers. That is, the availability of technology, the speed of access, the applications suited to the curriculum and to the pedagogical approach are, more and more, a harmonious set that is compatible with its mission. The study also clarifies that teachers intend to use ICT as they see in them a different didactic tool that allows different approaches, thus increasing, in general, the quality of teaching and learning.